Techniques and factors for reducing chronic neuropathic pain: A review - Damien P. Kuffler (Neural Regeneration Research, 2026)
Nerve trauma commonly results in chronic neuropathic pain. This is by triggering the release of pro-inflammatory mediators from local and invading cells that induce inflammation and nociceptive neuron hyperexcitability. Even without apparent inflammation, injury sites are associated with increased inflammatory markers. This review focuses on how it might be possible to reduce neuropathic pain by reducing inflammation. Physiologically, pain is resolved by a combination of the out-migration of pro-inflammatory cells from the injury site, the down-regulation of the genes underlying the inflammation, up-regulating genes for anti-inflammatory mediators, and reducing nociceptive neuron hyperexcitability. While various techniques reduce chronic neuropathic pain, the best are effective on < 50% of patients, no technique reliably or permanently eliminates neuropathic pain. This is because most techniques are predominantly aimed at reducing pain, not inflammation. In addition, while single factors reduce pain, increasing evidence indicates significant and longer-lasting pain relief requires multiple factors acting simultaneously. Therefore, it is not surprising that extensive data indicate that the application of platelet-rich plasma provides more significant and longer-lasting pain suppression than other techniques, although its analgesia is neither complete nor permanent. However, several case reports indicate that platelet-rich plasma can induce permanent neuropathic pain elimination when the platelet concentration is significantly increased and is applied to longer nerve lengths. This review examines the primary triggers of the development and maintenance of neuropathic pain and techniques that reduce chronic neuropathic pain. The application of platelet-rich plasma holds great promise for providing complete and permanent chronic neuropathic pain elimination.